The effectiveness of using children’s drawings in social care House in producing Purposeful digital stories - Al- Asqha, Shatha Brahim; Alqauimi, Ohood Mohammed (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to confirm the importance of art technology in the digital age by discovering the psychological and social ‏characteristics of children’s drawings during the dawning realism stage (7- 9 years old), at the Social Care House. The study also aimed to confirm the efficacy of these drawings for analyzing children’s personalities, their emotional and psychological states and art’s role in delivering a sociocultural message a digital storytelling method, which is in line with the requirements of KSA Vision 2030. By following the descriptive. The study reached a number of results, including the effectiveness of using children’s drawings in the production of digital stories. In addition, the imagination, which the societal environment to which it belongs affects it, is able to integrate with the indicative relationships in digital anthropology with its problematic implications in the production of digital stories that reveal psychological facts and social relationships in the daily life of a child in social care homes.